Análise da influência do combate a incêndio nas temperaturas de um compartimento - Kamyla Lima da Mata (2019)
In view of the importance of the study on the effects of conflagrations in compartments, especially with regard to structural aspects, the objective of this work was to develop a calibrated model by analyzing the influence of fire fighting types (interventions) in the temperatures of a compartment - type container - high cube, with approximately 28.3 m² of internal area, used as simulator of a real fire situation by the Minas Gerais Military Fire Departament of Brazil (CBMMG) during the training. For temperature monitoring, thermocouple sensors - type K (Cromel / Alumel) connected in five compartment sections, at respective heights: 0.80 m; 1.47 m; 2.15 m. The types of combat varied with the mode of application of water in simple pulses, two pulses or longer pulses. The results showed that the training represents well the real fires in building presenting the fire phases, ignition and growth, flashover and after flashover. As complementary part to this work, the results analyzed subsidiarity to computational simulations. Once validated, the methodology provides subsidies and encourages future research and experiments on the behavior of structures and building elements at high temperatures. Considering that, the determination of the actual temperature values and behavior - inside this sinister compartment - turned it into an oven adapted for controlled trials.